Problematika Penerapan Pasal 116 UU Peratun Terhadap Pelaksanaan Putusan PTUN - Habibi, Dani; Nuryani, Winda (TIN: Terapan Informatika Nusantara, 2020)
The State Administrative Court is one of the courts in Indonesia, which one of the tasks is to resolve cases in the field of state administration. The results of each deliberate settlement in court give rise to something that is mutually agreed upon by the judges, namely the so-called Court Decision. In contrast to court decisions from other courts such as the General Courts, Military Courts and Religious Courts, the State Administrative Court still has shortcomings in the process of implementing court decisions. This is because what is disputed is that it relates to decisions issued by state administrative officials, which in this case in Indonesia does not yet have an excess system of institutions which forces state administrative officials to re-make state administrative decisions in accordance with the provisions in court decisions. This study uses Normative Law research with a statutory approach. The results of this research are to describe the first, regarding the formulation of Article 116 which is contained in the Law on Administrative Courts, Second regarding the Problems with the Application of Article 116 of the Law on State Administrative Courts related to the implementation of court decisions